Public-private partnerships from the perspective of the national recovery and resilience plan - Ancuţa Marin; Steliana Rodino (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
Structured in two priority directions (reform and investment) The National Recovery and Resilience Plan is one meant to help communes, local communities in the crisis caused by COVID-19, as such any investment started after February 1, 2020, the date that is considered to be the beginning pandemic crisis, can be funded from this plan, if it complies with European regulations. Community development planning is a natural approach that aims to increase the quality of life and improve living conditions. However, the development of a community cannot be conceived in the absence of a vision of the directions in which the community wants and can develop. PNRR allocates substantial sums for the construction of water networks in rural areas, afforestation and the creation of protected areas, waste management, renewable energy, education, digital transition and last but not least research.The paper presents an analysis of areas where public-private partnerships can be created, especially in rural areas, to access these funds, as well as their importance in the rural economy.
Keywords: A19; R11; R12; 330; public-private partnerships; rural development; National Recovery and Resilience Plan